Хемингуэй на Кубе: очерки / Ю. Н. Папоров - Папоров Юрий Николаевич (Советский писатель, 1982)
Экземпляры: аб. (ретро) / Инвентарный номер: 4147 / Сис.шифр: 83.3(7Сое) / Авт.знак: П 17 / ББК: 83.3(7Сое)